2019
DOI: 10.1126/science.aaz4795
|View full text |Cite
|
Sign up to set email alerts
|

Cyber risk research impeded by disciplinary barriers

Abstract: Cyber risk encompasses a broad spectrum of risks to digital systems, such as data breaches or full-fledged cyber attacks on the electric grid. Efforts to systematically advance the science of cyber risk must draw upon not only computer science, but also fields such as behavioral science, economics, law, management science, and political science. Yet many scholars believe that they have sufficient understanding of other fields to comprehensively address the inherently cross-disciplinary nature of cyber risk. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 13 publications
1
26
0
3
Order By: Relevance
“…These diverse concerns mean that drawing researchers and practitioners from diverse disciplines is more likely to lead to success [73,35]. These HCAI systems will be well received if they go beyond statements about fairness, transparency, accountability, security, and privacy to support specific practices that raise human self-efficacy, encourage creativity, clarify responsibility, and facilitate social participation.…”
Section: Limitations Conclusion and Future Directionsmentioning
confidence: 99%
“…These diverse concerns mean that drawing researchers and practitioners from diverse disciplines is more likely to lead to success [73,35]. These HCAI systems will be well received if they go beyond statements about fairness, transparency, accountability, security, and privacy to support specific practices that raise human self-efficacy, encourage creativity, clarify responsibility, and facilitate social participation.…”
Section: Limitations Conclusion and Future Directionsmentioning
confidence: 99%
“…Sample period: N/A (7 months) Kamiya et al (2020) Conduct a comprehensive study that systematically evaluates both the likelihood and severity of data breaches as well as identifying the corresponding determinants. Sample period: 2005Sample period: -2017 Panel D: Cyber risk treatmentavoidance Falco et al (2019) Describe designing and using inherently secure systems as a type of risk avoidance. Sample period: N/A Toward the late 1990s, scholars from IT and other related disciplines eventually became aware of the lack of consistency and integrity in cataloging computer security risks and realized the need for a universal framework.…”
Section: Sample Period: N/amentioning
confidence: 99%
“…For example, research has shown that students have little understanding of agreed‐upon definitions in environmental and geographic education 9 and evolutionary biology 10 . Finally, definitional ambiguity in cybersecurity has recently been identified as one of the problems preventing the effective benchmarking of security across and within organizations 11 . In short, understanding definitional contexts is critical to effective STEM instruction 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…10 Finally, definitional ambiguity in cybersecurity has recently been identified as one of the problems preventing the effective benchmarking of security across and within organizations. 11 In short, understanding definitional contexts is critical to effective STEM instruction. 12,13 Although bioinformatics is frequently described in the literature, to the best of our knowledge, only two definitions of the field have been formally proposed (Table 1).…”
Section: Introductionmentioning
confidence: 99%